PENATAAN TAMAN BACA GRIO MUKTI UNTUK MENINGKATKAN LITERASI MEMBACA DI DESA PRINGOMBO KECAMATAN TEMPURAN - Eko Syahrul Jatmiko; Qurotul Aini; Dakusta Puspitasari (Institut Agama Islam Syubbanul Wathon Magelang, 2021)
Literacy is one of the main components in the development of human resources. However, Indonesian people have very low literacy. The study results show that the number of village taman baca is still very low. In addition, the reading facilities and infrastructure provided in the village reading park are also still limited. This community service activity aims to improve the management of the reading garden in Pringombo Village as an effort to improve literacy culture in the community. The method used is participation which involves the active participation of village government officials, the academic community, and the community. The stages of service activities carried out are observing, discussing, implementing, and socializing. The results of the village Taman Baca arrangement activities have been carried out in accordance with the plans and targets set, such as adding to the book collection, conducting an inventory, classification, and administration of the village Taman baca. Thus, the existence of the village reading park is expected to increase the reading literacy of the village community.